The mRNA Expression Profiles of Five Heat Shock Protein Genes from Frankliniella occidentalis at Different Stages and Their Responses to Temperatures and Insecticides - Hai-hong WANG; Stuart R Reitz; Li-xia WANG; Shuai-yu WANG; Xue LI; Zhong-ren LEI (Journal of Integrative Agriculture)
The western flower thrips, Frankliniella occidentalis (Pergande) is a highly invasive pest that is able to exploit many crops across a wide range of environmental conditions. Five full-length cDNAs of heat shock protein (HSP) genes (Fo-HSP90, Fo-HSP70, Fo-HSP60, Fo-HSP40 and Fo-HSP28.9) were cloned from F. occidentalis, and their expression profiles were investigated under conditions of thermal stress and insecticide exposure, and at different stages during development, using real-time quantitative PCR. All five gene sequences showed high similarity to homologs in other species, indicating the conserved function of this gene family. HSP60 represents an informative phylogenetic marker at the ordinal taxonomic level within Insecta, but HSP90, which has two homologous copies in Hymenoptera, was not informative. The expression of Fo-HSPs under thermal stress suggests that Fo-HSP90, Fo-HSP70, and Fo-HSP28.9 are inducible by both cold and heat stress, Fo-HSP40 is only heat-inducible, and Fo-HSP60 is thermally insensitive. There were two patterns of cold induction of Fo-HSPs: one is from 0 to 4°C and the other is around −8°C. All five Fo-HSPs genes were induced by exposure to sublethal concentrations of the insecticide avermectin. The expression of the five Fo-HSPs during different developmental stages suggests that they all play a role in development of F. occidentalis.